Growth and characterization of Ag–Al2O3 composites thin films for thermoelectric power generation applications. Issue 3 (1st February 2022) - Ullah, Inaam; Tamseel, M.; Amami, Mongi; Javed, Muhammad Rizwan; Javaid, K.; Mahmood, K.; Ikram, Salma; Ali, A.; Amin, N.; Hussain, M. Shujaat; Ali, M. Yasir; Arshad, M. Imran
Abstract: Thin films of Ag–Al2 O3 composites were successfully grown on Si substrate by thermal evaporation method and their thermoelectric performance was modulated using post growth annealing technique. Pellet of Ag and Al mixture having 1:4 ratio was evaporated on Si substrate using the vacuum tube furnace. As grown sample was cut into pieces and post-growth annealing was performed at different temperatures using muffle furnace. XRD results suggested that as-deposited sample has amorphous nature, but crystallinity of the samples increase as an annealing temperature increase from 600 to 900 o C. This structural behavior of annealed samples was further verified by Raman spectroscopy measurements. We have reported an optimal annealing temperature (800 0 C) for the best thermoelectric performance of investigated composites. At this specific annealing temperature, charge carriers are highly mobile which resulted in the enhancement of thermoelectric power generation performance of Ag–Al2 O3 composite. The value of power factor (1.38x10 −2  W/m-K −2 ) reported in the current study is the highest value for Ag–Al2 O3 composites so for reported in the literature according to the best of our knowledge.